PENERAPAN ARTIFICIAL INTELLIGENCE SERIAL VIDEO ANIMASI SUKACANTING DAN PELATIHAN KEMAMPUAN KOMUNIKASI - Stellarosa, Yolanda; Chrisdina, Chrisdina; Hutagaol, Olivia Deliani (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the national health problems that requires special attention and handling from various parties, namely from the central government, regional governments, and the family level, is stunting. Sukamulya Village is one of the villages in Rancaekek District, Bandung, West Java, located in the Citarum River watershed (DAS), which runs a stunting prevention program with three hamlets in it. Currently, one of the targets of stunting education is teenagers. The problem faced when targeting teenagers as targets for education and agents of change, especially in Sukamulya Village, is that the material on stunting has not been packaged with the approach style of teenagers who enjoy technology-based information. In addition, teenagers consider this unimportant because the education provided is too dull and delivered by people they feel are too old (the same age as their parents). So, a training activity was carried out to make an animated video series based on artificial intelligence (AI) called Sukacanting, a method of stunting education and public speaking training to improve public speaking skills in providing stunting prevention education. With the training and creation of AI-based animated videos, several Posyandu cadre youth have improved their skills in creating, managing, and developing health education videos and public speaking skills.